Child self-regulation in the school context : longitudinal trajectories over the early school transition years - Tan, Hui Xuan (Nanyang Technological University, 2021)
The ages between four to seven mark a vital period when children transit from informal to formal schooling contexts. These years are also a sensitive period where significant development in self-regulation occurs. However, groups of children can display distinct trajectories in the development self-regulation. Child demographic factors, such as gender and socio-economic status, can influence the level and shape of developmental trajectories. Hence, this study investigated the longitudinal trajectories of cognitive and emotional-behavioural self-regulation demonstrated by children in school contexts over the transition years. The presence of heterogeneity in longitudinal trajectories and the role of child demographic factors were also examined. Data for the current analysis was drawn from the Singapore Kindergarten Impact Project conducted by National Institute of Education. The current sample comprised 1399 children followed across three time points from Kindergarten 1 to Primary 1. Teacher-rated Behaviour Rating Inventory of Executive Function – 2nd Edition screening forms were used to access child self-regulatory difficulties. Analyses of the longitudinal trajectories were conducted using latent growth modelling. Findings show that children experience a non-linear increase in cognitive self-regulatory difficulties. Two trajectory classes were established: (a) high-and-stable, and (b) low-and-increasing. Boys and children with lower socio-economic status were more likely to belong to the former class. In contrast, children experience a linear decrease in emotional-behavioural self-regulatory difficulties. Two trajectory classes were established: (a) high-and-decreasing, and (b) low-and-stable. Boys and children with lower socio-economic status had higher odds of belonging to the former class. Implications and areas of further research are subsequently discussed.